Genome-wide haplotype-based association analysis of major depressive disorder in Generation Scotland and UK Biobank. Issue 11 (November 2017) - Howard, David; Hall, Lynsey; Hafferty, Jonathan; Zeng, Yanni; Adams, Mark; Clarke, Toni-Kim; Porteous, David; Nagy, Reka; Hayward, Caroline; Smith, Blair; Murray, Alison; Ryan, Niamh; et al.
Abstract Genome-wide association studies using genotype data have had limited success in the identification of variants associated with major depressive disorder (MDD). Haplotype data provide an alternative method for detecting associations between variants in weak linkage disequilibrium with genotyped variants and a given trait of interest. A genome-wide haplotype association study for MDD was undertaken utilising a family-based population cohort, Generation Scotland: Scottish Family Health Study (n  = 18, 773), as a discovery cohort with UK Biobank used as a population-based replication cohort (n  = 25, 035). Fine mapping of haplotype boundaries was used to account for overlapping haplotypes potentially tagging the same causal variant. Within the discovery cohort, two haplotypes exceeded genome-wide significance (P  < 5 × 10−8 ) for an association with MDD. One of these haplotypes was nominally significant in the replication cohort (P  < 0.05) and was located in 6q21, a region which has been previously associated with bipolar disorder, a psychiatric disorder that is phenotypically and genetically correlated with MDD. Several haplotypes withP  < 10−7 in the discovery cohort were located within gene coding regions associated with diseases that are comorbid with MDD. Using such haplotypes to highlight regions for sequencing may lead to the identification of the underlying causal variants.